Gestión del talento humano como estrategia para el desarrollo del desempeño laboral en la COAC Cámara de Comercio del cantón Bolívar - Cantos Loor, Diego Adrián (2023)
The research was carried out with the purpose of designing a Human Talent Management model as a strategy for the development of work performance in the Savings and Credit Cooperative Chamber of Commerce in Bolívar canton LTDA, for which a methodology with a mixed approach was used, in which a sample of 10 people was used, where the types of research used were field, descriptive and bibliographic, with analytical, inductive and deductive methods, whose phases included the following: (1) diagnosis of the current situation of the entity through the interview directed at the general manager, PESTEL SWOT analysis and performance evaluation with a survey used among collaborators; (2) determination and selection of the components to be developed in the model, carried out through a bibliographic review and a team of experts, (3) structuring of the model proposal under the guidelines and components defined by Chiavenato. The results determined that the cooperative presents weaknesses in the work performance of its collaborators, since 56% meet their productivity level well, while 44% show regular performance, therefore, these findings highlight the need to structure a human talent management model that strengthens the development of the work performance of its employees and therefore reflects a better corporate image. In conclusion, the design of the model based on Chiavenato's strategic processes, which encompass the provision, organization, retention, development and evaluation of the cooperative's staff, is expected to have a positive and significant impact within the entity in the long term.